Chaotic Conceptions of Good and Evil Presented in Game Of Thrones (TV Series) - Agatha Rakasiwi Cahya Nirvana; Atinia Hidayah (Metaphor, 2021)
The objectives of this study as it is mentioned in the problem statements is to analyze (1) the chaotic conception of good and evil presented in Game of Thrones (TV series), and (2) the conception of good and evil constructed in Game of Thrones. The method used in this research is qualitative approach. The object of this study is several episodes of Game of Thrones from season one to season eight. In collecting data, the techniques applied by the researcher are listening, reading, identifying, classifying, and selecting. The data analysis method is done by displaying, explaining, and interpreting. As a primary theory for the analysis, the researcher uses study of ethics by Peter Singer and Yaneer Bar-yam’s chaotic concepts. The results of the analysis shows that (1) the series presents chaotic conceptions of good and evil through the complex development of characters in Game of Thrones. (2) the series shows the construction of good and evil conception through four particular issues and cultural systems found in Game of Thrones, which are; how the culture enforce the law, the justice system, slavery, and trial by combat.